Clay body wrap with microcurrent: effects in central adiposity - Melo, Ana Sofia (2013)
Introduction Increased fat mass is becoming more prevalent in women and its accumulation in the abdominal region can lead to numerous health risks such as diabetes mellitus. The clay body wrap using compounds such as green clay, green tea and magnesium sulfate, in addition to microcurrent, may reduce abdominal fat mass and minimize or prevent numerous health problems. Objective This study aims at measuring the influence of the clay body wrap with microcurrent and aerobic exercise on abdominal fat. Methods Nineteen female patients, randomized into intervention (n = 10) and control (n = 9) groups, were evaluated using ultrasound for visceral and subcutaneous abdominal fat, calipers and abdominal region perimeter for subcutaneous fat and bioimpedance for weight, fat mass percentage and muscular mass. During 10 sessions (5 weeks, twice a week) both groups performed aerobic exercise in a cycloergometer and a clay body wrap with microcurrent was applied to the intervention group. Results When comparing both groups after 5 weeks of protocol, there was a significant decrease in the subcutaneous fat around left anterior superior iliac spine in the intervention group (ρ = 0.026 for a confidence interval 95%). When comparing initial and final abdominal fat in the intervention group, measured by ultrasound (subcutaneous and visceral fat) and by skinfold (subcutaneous fat), we detected a significant abdominal fat reduction. Conclusion This study demonstrated that the clay body wrap used with microcurrent and aerobic exercise can have a positive effect on central fat reduction.